(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Astuti I, Fadjar M, Nurdiani R, Sulistiyani TD. 2022. Mitochondrial cytochrome oxidase 1 (CO1) and morphology of Penja fish (Sicyopterus spp.) in Budong-Budong River, West Sulawesi, Indonesia. Biodiversitas 23: 4724-4729. Penja fish (local name) is a fish that is often found in West Sulawesi. Penja fish belong to the Goobidae family, which has a habit of migrating from the sea to the river. Penja fish species have not been widely published or in the Gen bank. The objective of this study was to analyze the Penja fish species found in the Budong-Budong river, West Sulawesi, Indonesia. The method used was a measurement of fish morphology and analysis of mitochondrial cytochrome oxidase I (COI) using a species barcode ( 700). Samples were taken from the catch of fishermen at the mouth of the Budong-Budong river. The result of morphological measurements obtained an average total length of 25-38 mm, standard length 22-35 mm, head length 2-5 mm, tail length 3-5 mm, pelvic fins 0.5-2 mm, pectoral fins 1-3 mm, dorsal fins 1-3 mm and anal fin 0.1-1 and body width 3-6 mm. Electrophoretic analysis on Penja fish samples showed that the DNA between P1 and P2 samples was not much different and has very small genetic variation in 696 bp fragment length. The analysis on the Basic Local Alignment Search Tool (BLAST) showed the identity percentage reached 99.85%. The Penja fish identified in the Budong-Budong river is of the family Gobiidae, genus Sicyopterus with the species name Sicyopterus pugnans, which is classified as post larva.